The Role of Virtual Teams in Increasing the Number of Innovations and Developing Competitive Advantage - Exploratory Data Analysis Study – - Mahdy, Fatimah Mohamed (Journal of Economic, Administrative and Legal Sciences, 2021)
This paper attempts to discover the role that virtual teams play in increasing the number of innovations in the research and development (R&D) department in global companies, and the extent to which this affects achieving a competitive advantage for the organizations under study (SAMSUNG, LG, IBM, and Toyota). The research was based on the method of exploratory analysis of data as the method of the study, and to achieve this goal, the researcher collected data on the number of hypothetical employees assigned to the research and development department in those companies compared to investments and sales and related to the number of innovations during the period between 2009- 2016. The research was based on the method of exploratory data analysis as a method for the study and analysis of the data used. The results of the research concluded that there is a positive direct relationship between the previous variables. Virtual teams are also one of the most important modern methods used in modern business enterprises and their necessity as a result of increasing response and shifting from serial work to simultaneous and parallel work to increase innovation, which leads to an increase in the competitive advantage of these organizations. The study recommends the need to pay attention to building effective virtual teams within organizations because of their essential advantages and to overcome the most important challenges that hinder the effectiveness and success of these teams. By increasing collaboration, interaction and efficiency leadership.